2020
DOI: 10.1021/acssensors.0c01404
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Nanobody-Based Fluorescent Immunosensor Mini Q-body for Rapid Signal-On Detection of Small Hapten Methotrexate

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information ABSTRACT: "Quenchbody (Q-body)" is a quench-based fluorescent biosensor labeled with a fluorescent dye near the antigen-binding site of an antibody. Q-bodies can detect a range of target molecules quickly by simply mixing with a sample. However, the development of Q-bodies using V HH -nanobodies derived from camelid heavy-chain antibodies has not been reported despite their favorable characteristics. Here, we report a "mini Q-body" that can dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…In addition, the yeast-displayed MTX nanobody showed antigen-binding activity (K D : 22.4 nM) (Supplementary Fig. S2), which was in good agreement with that previously described 11 . This suggests that a su cient amount of E4 peptide and MTX nanobody to evaluate the Q-body was displayed on the yeast cell surface without preventing antigen-binding activity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the yeast-displayed MTX nanobody showed antigen-binding activity (K D : 22.4 nM) (Supplementary Fig. S2), which was in good agreement with that previously described 11 . This suggests that a su cient amount of E4 peptide and MTX nanobody to evaluate the Q-body was displayed on the yeast cell surface without preventing antigen-binding activity.…”
Section: Resultssupporting
confidence: 90%
“…Assembly of Q-body on the yeast cell surface First, a nanobody-based Q-body was chosen as a candidate for displaying the Q-body because of its low molecular weight and high stability, which could be bene cial in the cloud of the yeast cell surface. In addition, the MTX-recognizing nanobody was previously proven to function as a Q-body with 6-fold response 11 , which suggested that MTX nanobody could be a suitable candidate for the proof-of-concept of the Q-body on the yeast cell surface. Also, an E4/K4 peptide pair was selected as a labeling tag because its high speci city and a nity will be suitable for assembling Q-bodies on the yeast cell surface, where various endogenous proteins coexist.…”
Section: Resultsmentioning
confidence: 99%
“…However, their applicability to camelid heavy-chain antibody variable domain (V HH or nanobody) has been elusive. Recently, nanobodies have received considerable attention owing to their small size (~14 kd) compared to scFv or Fab, and their high stability and resultant high production yield when produced in E. coli [49]. Since their first report, many examples of nanobodies that bind antigens specifically and strongly have been reported.…”
Section: Application To Nanobodiesmentioning
confidence: 99%
“…“Quenchbody (Q-body)” is an antibody-based novel fluorescent immunosensor, in which a fluorophore is labeled near the antigen-binding site of an antibody fragment such as a single-chain variable region (scFv) or Fab fragment 10 . Recently, an anti-methotrexate (MTX) nanobody (V HH ) has been proven to become a smaller Q-body (mini Q-body) 11 . We also found that several V H monodomains can be converted to mini Q-bodies (Banwait et al, in preparation).…”
Section: Introductionmentioning
confidence: 99%